The Development of a Cultural-Based Educational Program to Enhance Breast Self-Examination (BSE) Self-Efficacy - Juanita, Juanita; Jittanoon, Piyanuch; Boonyasopun, Umaporn (Nurse Media Journal of Nursing, 2012)
Purpose: To develop the educational program which is appropriate with Islamic culture in order to enhance BSE self-efficacy of nursing students and thus promote BSE practice. Method: This study is a development research study which is consisting of three phases including: 1) reviewing several existing BSE educational programs; 2) program design based on SCT and Islamic culture; and 3) program validation by three experts. Result: Based on previous studies, the most appropriate theory to enhance self-efficacy was Social Cognitive Theory (SCT) because this theory provides several strategies to increase the self-efficacy. Further, the program that used Islamic culture was more appropriate to increase BSE practice among Muslim women. As a result, the newly developed program was developed used SCT and Islamic culture. This program was comprised of four sessions including: 1) exploring Islamic mandate on prevention and individual responsibility in health promotion, and culture-related beliefs toward BSE, 2) health education by conducting lecturing session and watching a video about BSE procedures, 3) BSE training activities including BSE demonstration and return demonstration, 4) follow-up by conducting a meeting. Conclusion: The cultural-based educational program for enhancing BSE self-efficacy and promoting BSE is a program using multifaceted methods. It designed based on a review of the literature from previous studies and were supported by research findings on experimental studies in other population. Keywords: Cultural, Educational program development, Breast self-examination, Self-efficacy.